Flavonoids from Radix Tetrastigmae inhibit TLR4/MD-2 mediated JNK and NF-κB pathway with anti-inflammatory properties. (August 2016) - Liu, Dandan; Cao, Gang; Han, Likai; Ye, Yilu; SiMa, Yuhan; Ge, Weihong
Highlights: RTFs inhibit LPS-induced inflammation in macrophages. RTFs decrease pro-inflammatory factors production. RTFs increase anti-inflammatory cytokines secretion. RTFs block TLR4/MD-2 mediated pathway. RTFs reduce JNK phosphorylation and NF-κB activity. Abstract: Radix Tetrastigmae (RT) has immunomodulatory activity, particularly on inflammation and the flavonoids from RT (RTFs) are one of the main components. In this study, we detected the anti-inflammation potential of RTFs in LPS-induced RAW264.7 cells and tried to uncover the underlying mechanism. Results demonstrated that RTFs (10–160 μg/ml) treatment significantly decreased LPS-induced production of pro-inflammatory mediators, including NO, IL-1β, TNF-α, IL-6, IL-12p40, sTNF-R1 and increased anti-inflammatory cytokine IL-10 expression in macrophages in a dose-dependent manner. Molecular research showed the up-regulated expression of TLR4, MD-2, MyD88 and TLR4/MD-2 complex induced by LPS were attenuated after RTFs treatment. Furthermore, phosphorylation and activity of JNK and NF-κB, two important downstream signaling molecules of TLR4/MD-2 pathway, were also changed along with TLR4/MD-2 complex. But no significant phosphorylation was observed on p38 and ERK. In conclusion, RTFs contribute to the regulation of LPS-induced inflammatory response in RAW264.7 cells through TLR4/MD-2 mediated NF-κB and JNK pathway. It may be a potential choice for the treatment of inflammation diseases.